Risk factors associated with multidrug-resistant pulmonary tuberculosis in patients over 15 years old: a retrospective case-control study - Receado, Odete Bambi; Solary, Paulo Ney; Catumbela, Emanuel; Sousa, Carlos Alberto Pinto de (Frontiers in Tuberculosis, 2025)
IntroductionMultidrug-Resistant Pulmonary Tuberculosis (MDR-TB) represents a serious public health problem, hindering disease control and increasing morbidity and mortality. This study aimed to identify risk factors associated with MDR-TB in patients over 15 years old at the Sanatorium Hospital of Luanda during the period 2015–2016.MethodsA retrospective case-control study (1:1) was conducted with 500 participants, including 250 cases (MDR-TB) and 250 controls (drug-sensitive TB). Data were obtained from clinical records and analyzed using logistic regression in Epi-Info 7.2.1.0 software, considering a significance level of p < 0.05.ResultsMDR-TB was more prevalent in men (61.6%), in the age group 20–29 years (36.8%), and among employed individuals (73.2%). The associated risk factors were irregular medication adherence [odds ratio (OR) = 12.3; p < 0.001], previous TB treatment (OR = 9.0; p < 0.001), contact with an MDR-TB patient (OR = 4.1; p < 0.001), and lower educational level (OR = 2.1; p = 0.03).ConclusionIrregular adherence to treatment and a history of previous TB were the main factors associated with MDR-TB, reinforcing the need for effective strategies to ensure treatment follow-up.